Analysis of cutting-oil emulsion destabilization by aluminum sulfate. Issue 11 (3rd June 2018) - Chawaloesphonsiya, Nattawin; Guiraud, Pascal; Painmanakul, Pisut
ABSTRACT: The destabilization mechanism of the high stable cutting-oil emulsion by aluminum sulfate (Al2 (SO4 )3 ) was investigated since it can affect properties of aggregates and following separation units. Al2 (SO4 )3 dosage and pH were key factors in the destabilization. The effective separation occurred when precipitated Al(OH)3 is dominated at the neutral pH of 6.5–7.0. The best separation can be achieved when solid flocs were formed at 1.0 mM, which exceeded the dosage from the critical coagulation concentration (CCC) of 0.75 mM. Two different mechanisms were proved for the emulsion destabilization depending upon the Al 3+ concentration under this pH range. The first mechanism was the adsorption of Al(OH)3 on surface of oil droplets, which led to the droplet coalescence. By increasing the Al 3+ dosage, the sweep flocculation by Al(OH)3 precipitates occurred. Al 3+ dosage for effective destabilization was increased in accordance with oil concentration. The formation of aluminum hydroxide precipitates in bayerite structure was affirmed by analyzing elemental composition and crystalline structure of flocs from the destablization.